Scratching a Niche: How Smaller Social Media Players Such as Dribbble Reflect the Viral Phenomenon. (November 2019) - Hemsley, Jeff; Kelly, Rebecca D.
Researchers have been studying the viral flow of information since the late 1990s, but this work has mainly focused on big sites like Twitter and Facebook. However, to comprehensively explore social phenomena such as virality requires us to look beyond the dominant networks. This study addresses this by looking at how users think about virality on Dribbble, a social network site with around 600, 000 users that was created in 2009 for designers to showcase and get feedback on their work and to connect clients to design talent. Interviews confirm that viral-like events do exist on Dribbble. Our informants suggest that what spreads on Dribbble are elements of design (e.g., color palettes, line styles, textures), and they identify a number of factors they believe drive these viral-like events, which are the same kinds of factors that drive virality on larger sites. We briefly discuss how Dribbble feeds the gig economy in the creative industry and how virality becomes an important path for designers in a competitive environment. This work makes a contribution to the study of virality by focusing a small niche social media site and by looking at how users perceive and think about viral events.